2017
DOI: 10.17219/acem/42197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the infliximab therapy of severe form of pediatric Crohn’s disease in Poland: Retrospective, multicenter studies

Abstract: Background. Pediatric ulcerative colitis (UC) is a severe disease characterised by the presence of extensive inflammatory lesions in the colon. The administration of intravenous corticosteroids is recommended in patients with acute relapse of the disease, whereas early treatment with cyclosporine, tacrolimus or infliximab is recommended if there is no improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Stern et al showed that, in pediatric patients with TA, infliximab was as effective as cyclophosphamide with fewer side effects and thus is a viable alternative to treatment of pediatric TA [27]. Iwańczak et al has shown that children with moderate to severe ulcerative colitis have achieved remission with infliximab, and it was effective in preventing early colectomy [28]. Eleftheriou et al completed a retrospective descriptive case series of four children with CRMO or synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome treated with TNF alpha blockade and found that disease activity was improved for 3 of 4 children at 12 months after starting biologic therapy and the fourth discontinued therapy due to a suspected fungal skin infection [29].…”
Section: Discussionmentioning
confidence: 99%
“…Stern et al showed that, in pediatric patients with TA, infliximab was as effective as cyclophosphamide with fewer side effects and thus is a viable alternative to treatment of pediatric TA [27]. Iwańczak et al has shown that children with moderate to severe ulcerative colitis have achieved remission with infliximab, and it was effective in preventing early colectomy [28]. Eleftheriou et al completed a retrospective descriptive case series of four children with CRMO or synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome treated with TNF alpha blockade and found that disease activity was improved for 3 of 4 children at 12 months after starting biologic therapy and the fourth discontinued therapy due to a suspected fungal skin infection [29].…”
Section: Discussionmentioning
confidence: 99%
“…A 2011 systematic review showed a 1-year response rate of 64% ( 12 ). Other studies have demonstrated long-term response rates from 57 to 61% ( 16 , 23 ) in paediatric UC. In contrast, data from this study also suggest a less favourable response to steroids in Irish children with ASC.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that TNF-α levels are significantly increased in IBD patients (Murch et al, 1993; Billmeier et al, 2016). The treatment of IBD patients with TNF-α monoclonal antibody (such as infliximab and golomumab) could effectively alleviate the disease (Rutgeerts et al, 2005; Sandborn et al, 2014; Iwanczak et al, 2017). In addition, IL-10 is an important anti-inflammatory cytokine in the body.…”
Section: Discussionmentioning
confidence: 99%